Massive active population inquiry for COVID-19. Experience with medical science students. Cienfuegos, 2020 - Arelys Falcón Hernández; Victor René Navarro Machado; Alexis Díaz Brito; Hilda María Delgado Acosta; María Lina Valdés Gómez (Medisur)
Foundation: active inquiry allows an early health status diagnosis of population groups. Objective: to describe the process of active research in the population to detect possible cases of COVID-19. , carried out by students of medical sciences. Methods: prospective, descriptive, cross-sectional study, carried out at the Cienfuegos University of Medical Sciences, Cuba, between March 19 and April 18, 2020 by 2,280 students and 142 teachers. Techniques: participatory observation and daily reports of research activity. Results: between 795 and 2,186 students have progressively participated in daily research activities, which ranged from 91-92% of the students called. On average, 61 189 homes were visited daily and 114 491 inhabitants were surveyed (28.13% of the total population); Out of these, 11 were positive and 27 were suspected of the disease. COVID-19 has not been reported among students. Conclusion: massive community active research has quadrupled in its first month and has contributed to the early detection of acute respiratory infections related to COVID-19 in the Cienfuegos province. The research process has been safe for students and teachers, who were trained in aspects related to disease transmission and biosecurity measures.